Larval Development of Aedes aegypti and Aedes albopictus in Peri-Urban Brackish Water and Its Implications for Transmission of Arboviral Diseases - Ramasamy, R.; Surendran, S.N.; Jude, P.J.; Dharshini, S.; Vinobaba, M. (PLoS, 2011)
Aedes aegypti (Linnaeus) and Aedes albopictus Skuse mosquitoes transmit serious human arboviral diseases including yellow fever, dengue and chikungunya in many tropical and sub-tropical countries. Females of the two species have adapted to undergo preimaginal development in natural or artificial collections of freshwater near human habitations and feed on human blood. While there is an effective vaccine against yellow fever, the control of dengue and chikungunya is mainly dependent on reducing freshwater preimaginal development habitats of the two vectors. We show here that Ae. aegypti and Ae. albopictus lay eggs and their larvae survive to emerge as adults in brackish water (water with ,0.5 ppt or parts per thousand, 0.5–30 ppt and .30 ppt salt are termed fresh, brackish and saline respectively). Brackish water with salinity of 2 to 15 ppt in discarded plastic and glass containers, abandoned fishing boats and unused wells in coastal peri-urban environment were found to contain Ae. aegypti and Ae. albopictus larvae. Relatively high incidence of dengue in Jaffna city, Sri Lanka was observed in the vicinity of brackish water habitats containing Ae. aegypti larvae. These observations raise the possibility that brackish water-adapted Ae. aegypti and Ae. albopictus may play a hitherto unrecognized role in transmitting dengue, chikungunya and yellow fever in coastal urban areas. National and international health authorities therefore need to take the findings into consideration and extend their vector control efforts, which are presently focused on urban freshwater habitats, to include brackish water larval development habitats